Oil Price Volatility and Real Effective Exchange Rate: The Case of Thailand - Jiranyakul, Komain (International Journal of Energy Economics and Policy, 2015)
The main objective of this study is to directly examine the relation between real oil price and real effective exchange rate in Thailand during July 1997 to December 2013. Under the floating exchange rate regime, bilateral exchange rates are expected to fluctuate more than under the fixed exchange rate regime. The monthly data of real effective exchange rate index and real oil price are used. The results from this study reveal that there is no cointegration and causality in levels of the two series. However, an increase in oil price volatility causes real exchange rate volatility to increase. This main finding gives some policy implications to policy makers. Keywords: Oil price; real exchange rate; bivariate GARCH; volatility spillover. JEL Classifications: C22; G40